2023
DOI: 10.3389/fpls.2023.1258023
|View full text |Cite
|
Sign up to set email alerts
|

PSTVd infection in Nicotiana benthamiana plants has a minor yet detectable effect on CG methylation

Martha Tselika,
Nektarios Belmezos,
Paraskevi Kallemi
et al.

Abstract: Viroids are small circular RNAs infecting a wide range of plants. They do not code for any protein or peptide and therefore rely on their structure for their biological cycle. Observed phenotypes of viroid infected plants are thought to occur through changes at the transcriptional/translational level of the host. A mechanism involved in such changes is RNA-directed DNA methylation (RdDM). Till today, there are contradictory works about viroids interference of RdDM. In this study, we investigated the epigenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 96 publications
(192 reference statements)
0
0
0
Order By: Relevance
“…However, it should be noted that the algorithm is based on the hypothesis that vd‐sRNA affects the host genome and transcripts through RNA silencing, although no study to date provides conclusive evidence that vd‐sRNA can directly induce host transcript cleavage. Additionally, recent studies have reported that PSTVd may disrupt global alternative splicing of host transcripts (Zheng et al., 2017 ), alter global host genome methylation patterns (Tselika et al., 2023 ), and interfere with the host's endogenous factors involved in replication and transport (Ma et al., 2023 ). Thus, viroid pathogenicity extends beyond simple disruptions of gene regulations via RNA silencing.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the algorithm is based on the hypothesis that vd‐sRNA affects the host genome and transcripts through RNA silencing, although no study to date provides conclusive evidence that vd‐sRNA can directly induce host transcript cleavage. Additionally, recent studies have reported that PSTVd may disrupt global alternative splicing of host transcripts (Zheng et al., 2017 ), alter global host genome methylation patterns (Tselika et al., 2023 ), and interfere with the host's endogenous factors involved in replication and transport (Ma et al., 2023 ). Thus, viroid pathogenicity extends beyond simple disruptions of gene regulations via RNA silencing.…”
Section: Discussionmentioning
confidence: 99%